The Association between Serum Follicle-Stimulating Hormone Levels and the Success of Microdissection Testicular Sperm Extraction in Patients with Azoospermia - Yildirim, Mehmet Erol; Koc, Akif; Koc, Akif; Kaygusuz, Ikbal Cekmen; Kaygusuz, Ikbal Cekmen; Badem, Hüseyin; Badem, Huseyin; Karatas, Omer Faruk; Karatas, Omer Faruk; Cimentepe, Ersin; Cimentepe, Ersin; Unal, Dogan; et al. (Urology Journal, 2014)
Purpose: To evaluate the predictive power of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, testicular biopsy histology and male age were evaluated with respect to the success of sperm retrieval in a microdissection testicular sperm extraction (microTESE) procedure, pregnancy and live birth rates. Materials and Methods: We examined the data of 131 infertile men with non-obstructive azoospermia, who have undergone microTESE operation. The men were classified into two groups based on serum follicle-stimulating hormone (FSH) levels ≤ 15 mIU/mL (group 1) and > 15 mIU/mL (group 2). Results: Group 1 consisted of 59 patients (mean age 36.2 ± 6.2 years) and group 2 consisted of 72 (mean age 38.8 ± 7.4 years) patients. Sperm retrieval and pregnancy rates were 66.1% and 16.9% in normal FSH group, respectively. These parameters were higher than those of men with FSH > 15 (43% and 8.3%, respectively). Only 128 patients had histopathological diagnosis. Sperm was retrieved from 12/30 (40%) patients with maturation arrest, 9/29 (31.03%) patients with seminiferous tubules atrophy, 14/40 (35%) patients with sertoli cell only syndrome and 13/13 (100%) of patients with hypospermatogenesis. There was no statistically significant difference in pathological diagnosis between pregnancy and live birth rates. Conclusion: These results demonstrate that there is a significant difference with sperm retrieval, pregnancy rates and live birth rates comparing the FSH levels. Histopathological findings did not associate with successful microTESE, pregnancy rates and live birth rates.